2016
DOI: 10.5194/bg-13-4461-2016
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical and biological impacts of diazotroph blooms in a low-nutrient, low-chlorophyll ecosystem: synthesis from the VAHINE mesocosm experiment (New Caledonia)

Abstract: Abstract. In marine ecosystems, biological N 2 fixation provides the predominant external source of nitrogen (N; 140 ± 50 Tg N yr −1 ), contributing more than atmospheric and riverine inputs to the N supply. Yet the fate and magnitude of the newly fixed N, or diazotroph-derived N (hereafter named DDN) in marine ecosystems is poorly understood. Moreover, whether the DDN is preferentially and directly exported out of the photic zone, recycled by the microbial loop and/or transferred into larger organisms remains… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 105 publications
1
10
0
Order By: Relevance
“…This result is in accordance with high export fluxes measured in the tropical North Atlantic when the diazotroph community is dominated by DDAs (Subramaniam et al, 2008;White et al, 2012). More recently, Berthelot et al (2015) and Bonnet et al (2016a) studied the fate of a bloom of unicellular diazotrophs from Group C (UCYN-C) during a mesocosm experiment in the New Caledonia lagoon after a phosphate enrichment and revealed that ∼ 10 % of UCYN-C from the water column was exported to the particle traps daily, representing as much as 22.4 ± 5.5 % of the total POC exported at the height of the UCYN-C bloom. A δ 15 N budget performed in the mesocosms confirmed the high contribution of N 2 fixation (56 %; Knapp et al, 2016) to export compared to other tropical and subtropical regions where active N 2 fixation contributes 10 to 25 % to export production (e.g., Altabet, 1988;Knapp et al, 2005) and exceptionally up to 92 % in the Arabian Sea (Gandhi et al, 2011;Kumar et al, 2017).…”
Section: General Contextsupporting
confidence: 89%
See 1 more Smart Citation
“…This result is in accordance with high export fluxes measured in the tropical North Atlantic when the diazotroph community is dominated by DDAs (Subramaniam et al, 2008;White et al, 2012). More recently, Berthelot et al (2015) and Bonnet et al (2016a) studied the fate of a bloom of unicellular diazotrophs from Group C (UCYN-C) during a mesocosm experiment in the New Caledonia lagoon after a phosphate enrichment and revealed that ∼ 10 % of UCYN-C from the water column was exported to the particle traps daily, representing as much as 22.4 ± 5.5 % of the total POC exported at the height of the UCYN-C bloom. A δ 15 N budget performed in the mesocosms confirmed the high contribution of N 2 fixation (56 %; Knapp et al, 2016) to export compared to other tropical and subtropical regions where active N 2 fixation contributes 10 to 25 % to export production (e.g., Altabet, 1988;Knapp et al, 2005) and exceptionally up to 92 % in the Arabian Sea (Gandhi et al, 2011;Kumar et al, 2017).…”
Section: General Contextsupporting
confidence: 89%
“…Mechanistically, the vertical downward flux was enabled by the aggregation of the small (5.7 ± 0.8 µm) UCYN-C cells into large (100-500 µm) aggregates. In addition to direct export of diazotrophs, the use of nanoSIMS (nanoscale secondary ion mass spectrometry) enabled the tracking of the fate of 15 N from both Trichodesmium (Bonnet et al, 2016b) and UCYN blooms (Berthelot et al, 2015;Bonnet et al, 2016c) and demonstrated that ∼ 8 % of N originating from N 2 fixation is quickly transferred to non-diazotrophic plankton, in particular diatoms, i.e., efficient C exporters to depth (Nelson et al, 1995) during Trichodesmium blooms (Bonnet et al, 2016b). This reveals that N 2 fixation can fuel large-size nondiazotrophic plankton growth in the water column, suggesting an indirect export pathway of organic matter sustained by N 2 fixation in the oligotrophic ocean.…”
Section: General Contextmentioning
confidence: 99%
“…UCYN-C is the least studied and descriptions about UCYN-C are rare. These three groups of UCDs may form blooms or dominate diazotrophic community in oligotrophic waters (Robidart et al, 2014;Bonnet et al, 2016;Wilson et al, 2017). Among the groups of the UCDs, only the UCYN-B (i.e., Crocosphaera watsonii) is cultivated.…”
Section: Introductionmentioning
confidence: 99%
“…Trichodesmium has a ubiquitous distribution throughout tropical and subtropical oceans where it contributes substantial amounts of new nitrogen (N) to the oligotrophic near-surface ocean through dinitrogen (N 2 ) fixation [1,2]. In the North Pacific Subtropical Gyre, Trichodesmium is suggested to account for up to half of the biologically fixed N 2 [3], which generally mitigates N limitation, and even promotes the growth of a broader plankton community [4][5][6] and eventual carbon (C) export to the deep sea [7][8][9]. Trichodesmium grows as filaments, referred to as trichomes, which at times aggregate as millimetre-sized spindle-shaped (tufts) or spherical (puffs) colonies [10], often forming conspicuous blooms which can be observed from space [11].…”
Section: Introductionmentioning
confidence: 99%